Strategi Pembinaan dan Manajemen Organisasi PMR dalam Membangun Karakter Peserta Didik Ditingkat Mula Di SDN 060913 - Siswanti, Nadila (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Science has developed so rapidly, as has technology that brings challenges in the world of education, where academic orientation often ignores spiritual values, thus potentially producing individuals who are intelligent but morally weak. The purpose of this study is to analyze the integration of monotheistic values in student learning in schools in Indonesia and its role in shaping student character. Using a qualitative literature study method, this study examines Islamic literature such as the Qur'an, Hadith, and works of Muslim scientists, as well as secondary sources in the form of journals and academic articles. Content analysis techniques are applied to compile a conceptual synthesis of the integration of monotheistic knowledge and science. The results of the study indicate that monotheistic knowledge, as the main foundation of Islamic teachings, can be integrated through a holistic approach in the curriculum, such as integrating verses of the Qur'an in science and language lessons, and implementing learning methods that instill values of faith, such as honesty and discipline. This approach has been proven to increase students' noble morals, self-confidence, and spiritual awareness, although challenges such as the dichotomy of religious and general knowledge and the influence of global culture still need to be overcome. The impact, Education based on tauhid will produce a generation that not only has academic ability but also has good morality, which is able to face contemporary challenges that have an Islamic character.